2022
DOI: 10.3390/cells11142207
|View full text |Cite
|
Sign up to set email alerts
|

Ferroptosis-Related Genes Are Potential Therapeutic Targets and the Model of These Genes Influences Overall Survival of NSCLC Patients

Abstract: Background: Lung adenocarcinoma (LUAD) and lung squamous cell carcinoma (LUSCC) are two of the most common subtypes of non-small cell lung cancer (NSCLC), with high mortality rates and rising incidence worldwide. Ferroptosis is a mode of programmed cell death caused by lipid peroxidation, the accumulation of reactive oxygen species, and is dependent on iron. The recent discovery of ferroptosis has provided new insights into tumor development, and the clinical relevance of ferroptosis for tumor therapy is being… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Numerous studies have shown that ferroptosis is associated with various human diseases, including cancer, neurodegenerative diseases, ischemic reperfusion injury, and renal degeneration [28,29]. The glutathione peroxidase 4 (GPX4) pathway plays a central role in regulating ferroptosis, as evidenced by the cysteine/glutamate reverse transporter system X [30,31]. In this study, the ZDHHC16 gene reduced ferroptosis of NSCLC by the rehabilitation of mitochondrial structure.…”
Section: Discussionmentioning
confidence: 85%
“…Numerous studies have shown that ferroptosis is associated with various human diseases, including cancer, neurodegenerative diseases, ischemic reperfusion injury, and renal degeneration [28,29]. The glutathione peroxidase 4 (GPX4) pathway plays a central role in regulating ferroptosis, as evidenced by the cysteine/glutamate reverse transporter system X [30,31]. In this study, the ZDHHC16 gene reduced ferroptosis of NSCLC by the rehabilitation of mitochondrial structure.…”
Section: Discussionmentioning
confidence: 85%
“…EGCG is considered the most abundant compound in green tea and is effective in treating several diseases, including NSCLC [ 27 ]. Ferroptosis, a novel form of regulated cell death, has emerged as an attractive therapeutic target in cancer, including NSCLC [ 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Ferroptosis refers to an iron dependent oxidative form of regulated cell death and plays dual roles in tumorigenesis by modulating tumor microenvironment and tumor immunity [61]. The expression pattern, prognostic value and mechanistic analysis of ferroptosis related genes have been initially explored in LUAD [62][63][64]. In our study, iron death was more closely linked to the protective role of STARD12, which may participate in the regulation of nine ferroptosis associated genes including ALOX15, DPP4, GLS2, NCOA4, ATP5MC3, CARS1, CISD1, FANCD2 and SLC7A1 to suppress tumor progression of LUAD.…”
Section: Discussionmentioning
confidence: 99%